2006
DOI: 10.1007/s11661-006-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of iron aluminum alloy/steel laminate by clad rolling

Abstract: Laminates of an iron-aluminum alloy (20Al) and three types of steel-chromium molybdenum (CrMo), high carbon (FeCMn), and precipitation hardening steel with niobium carbide (FeCNb)-were fabricated at 600°C and 1000°C by clad rolling based on the compression stress ratio of 20Al to steel. The laminates fabricated at 600°C exhibit a deformation microstructure with partial recrystallization, while those at 1000°C reveal a refined microstructure. The 20Al layer of all the laminates exhibit a {001}AE110ae texture, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Masahashi et al [5,6] reported that simultaneous deformation together with soft material is a beneficial method to deform hard material by stress relief, even though the plastic instabilities in one of the components happen earlier than the other one due to prominent differences in mechanical properties [23] . Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Masahashi et al [5,6] reported that simultaneous deformation together with soft material is a beneficial method to deform hard material by stress relief, even though the plastic instabilities in one of the components happen earlier than the other one due to prominent differences in mechanical properties [23] . Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, the true stress-strain curve of the laminated composite shows a different flow pattern in three typical features: (i) the flow behaviour is mild without stress saltation, which is conducive to reduce the crack sensitivity, (ii) the peak value of the true stress is ~108 MPa at true strain of ~0.4. Considerable lower stress combined with higher plastic strain signifies the soft claddings contributed to stress relief during simultaneous deformation [5,6] . (iii) A steady state rather than a sharp decrease of the true stress is displayed over the peak value.…”
Section: Hot Deformation Of the Laminatementioning
confidence: 99%
See 2 more Smart Citations
“…Multi-layered metals artificially constructed by brittle and ductile layers are of interest because of their good fracture properties, unique mechanical behaviors, [1][2][3][4][5][6][7][8] and further possibilities to attain functional properties such as corrosion resistance. As a pioneering work, Sherby et al investigated mechanical behaviors of laminated composites fabricated by a rolling; e.g., the composites constructed by ultrahigh-carbon-steel/mild-steel 9) and by ultrahigh-carbonsteel/brass.…”
Section: Introductionmentioning
confidence: 99%